Xenbase: a genomic, epigenomic and transcriptomic model organism database. Issue Volume 46:Issue D1(2018) (20th October 2017) - Karimi, Kamran; Fortriede, Joshua D; Lotay, Vaneet S; Burns, Kevin A; Wang, Dong Zhou; Fisher, Malcom E; Pells, Troy J; James-Zorn, Christina; Wang, Ying; Ponferrada, V G; Chu, Stanley; Chaturvedi, Praneet; et al.
Abstract: Xenbase (www.xenbase.org ) is an online resource for researchers utilizing Xenopus laevis and Xenopus tropicalis, and for biomedical scientists seeking access to data generated with these model systems. Content is aggregated from a variety of external resources and also generated by in-house curation of scientific literature and bioinformatic analyses. Over the past two years many new types of content have been added along with new tools and functionalities to reflect the impact of high-throughput sequencing. These include new genomes for both supported species (each with chromosome scale assemblies), new genome annotations, genome segmentation, dynamic and interactive visualization for RNA-Seq data, updated ChIP-Seq mapping, GO terms, protein interaction data, ORFeome support, and improved connectivity to other biomedical and bioinformatic resources.